Public Organizational Resilience in Facing Digital Transformation in Indonesia - Sovia Rosalin; Denok Sunarsi; Dodi Ilham Mustaring (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2026)
Digital transformation has become a strategic agenda in public sector reform; however, its success largely depends on the organization’s ability to adapt to change. This study aims to analyze organizational resilience in the context of digital transformation and to identify the factors influencing it. A qualitative approach with a case study design was employed, with data collected through in-depth interviews, document analysis, and observation. The findings reveal that organizational resilience is shaped by the interaction of adaptive leadership, innovation-oriented organizational culture, digital capability, and institutional support. Leadership plays a critical role in guiding transformation and reducing resistance, while a flexible organizational culture promotes continuous learning and adaptation. Furthermore, digital competencies and technological infrastructure are essential in supporting the implementation of digital transformation, reinforced by adequate policies and resources. This study highlights that digital transformation is not merely about technology adoption but also requires strengthening organizational resilience, particularly in developing countries facing resource constraints and digital divides.